2015
DOI: 10.1163/1568539x-00003238
|View full text |Cite
|
Sign up to set email alerts
|

Changes to web architecture of Leucauge volupis (Araneae: Tetragnathidae) induced by the parasitoid Hymenoepimecis jordanensis (Hymenoptera: Ichneumonidae)

Abstract: Some new cases of ectoparasitoid wasps from the Polysphincta genus-group manipulating the behaviour of host spiders have been described in recent years, indicating that the modification of normal web structure is the rule rather than an exception as the outcome of these interactions. In most cases, orb web diameter and the number of adhesive spirals are reduced, which decreases the probability of web damage from the interception of insects on the viscid threads during the development of the parasitoid within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Probably the reduction in the number of radii and sticky spirals determine the reduction in the odds of insect interception, which would result in damages or even in web destruction (Gonzaga et al 2015). The attachment of the cocoon to this structure may also prevent the cocoon from falling on the ground.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably the reduction in the number of radii and sticky spirals determine the reduction in the odds of insect interception, which would result in damages or even in web destruction (Gonzaga et al 2015). The attachment of the cocoon to this structure may also prevent the cocoon from falling on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…He suggested that this modified web is very similar to build by spiders in juvenile stages of development. In the fourth case, Gonzaga et al 2015 collected adults and sub-adults of L. volupis (Keyserling. 1893) parasitized by H. jordanensis Loffredo & Penteado-Dias, 2009 in Minas Gerais state.…”
Section: Introductionmentioning
confidence: 99%
“…Cocoon webs appear to be more resistant to rupture [18,20,21] and have fewer components (e.g., radii and sticky spirals in orb webs) that are utilized for prey interception and retention. Variations of this general pattern include the addition of barrier threads [22], shorter radii, doubled number of lines in each radius, construction of a reinforced frame [19], reinforcement of the retreat by addition of more threads [14] or a veil sheltering the cavity containing spider and larva [23]. These alterations are not a by-product of infection [20,21], but appear to be directly induced by the parasitoid larva.…”
Section: Introductionmentioning
confidence: 99%
“…A similar 2D cocoon web is built by the related species Leucauge roseosignata Mello-Leitão, 1943 manipulated by Hymenoepimecis japi Sobczak, Loffredo, Penteado-Dias and Gonzaga, 2009(Sobczak et al 2009. A similar 2D architecture of the cocoon web, but protected by the 3D structure of the tangle positioned below the hub, was recently described in the spider hosts Leucauge mariana (Keyserling, 1881) manipulated by Hymenoepimecis tedfordi Gauld, 1991 (Eberhard 2013) and Leucauge volupis (Keyserling, 1893) manipulated by Hymenoepimecis jordanensis Loffredo & Penteado-Dias, 2009 (Gonzaga et al 2014). In contrast, the larva of Eruga gutfreundi Gauld, 1991 induced the same host (L. mariana) to build a completely different three-dimensional cocoon web (hereafter 3D) (Eberhard 2013).…”
Section: Introductionmentioning
confidence: 77%